Database Research in Spine Surgery. Issue 10 (December 2016) - Sebastian, Arjun S.
Abstract : With the introduction of several publicly available national databases to study surgical outcomes, the use of such databases for spine surgery research has increased dramatically. These databases allow researchers to retrospectively examine data from a large sample of patients. This rise in the use of national databases to study surgical outcomes parallels an increasing reliance by administrators, payers, and third-party graders to evaluate surgical quality with the use of large administrative databases. A good understanding of the most commonly utilized databases for spine surgery is important for critical assessment of this growing body of literature.